ANALISIS PERMINTAAN PASAR EKSPOR TERHADAP PRODUK UDANG BEKU INDONESIA - Oni Fajar Syahfdi; Akbar Siregar; Azwar Hamid (Universitas Medan Area, 2018)
In general, the destination of this thesis is to know the factors influencing of demand to the Indonesian frozen shrimp/prawn, and specially is to analyse the influence of the Indonesian frozen shrimp/prawn price variable, frozen shrimp/prawn price of competitor (Vietnam and Thailand), income and mount the consumption per capita, and also number of the consumer of chosen exporting destination countries (Japan and America). The analysis of this research is using by the applied of demand theory with double of natural logarithm model and processed with of Ordinary of Least Square method. The result show that's not all variable show the marking matching or have the same sign with hypothesis. The sign of signification and the sign of elasticity of variable has watch from demand choice of export destination country has made different. For Japan's shrimp market, the variable matching or have the same sign with hypothesis are frozen shrimp/prawn price of Indonesia, and mount the earnings (income) per capita. While for American's shrimp market, the variable matching or have the same sign with with hypothesis are frozen shrimp/prawn price of Indonesia, frozen shrimp/prawn price of the competitor country (Thailand), mount the earnings (income) and mount the consumption per capita. The others is disagree with formulated hypothesis.